Probable Neonatal Sepsis : A Retrospective Cross-Sectional Study In Indonesia - Nurul Damayanti; Lendy Nugroho; Monique Noorvitrry; Nursela Hijriani; Irsan Fahmi A (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2026)
Background: Neonates have an immature immune system, making them highly susceptible to infections that can rapidly progress to sepsis and death if not promptly treated. Empiric antibiotics play a critical role in the initial management of neonatal sepsis. However, there is limited local evidence regarding the evaluation of empiric antibiotic therapy in probable neonatal sepsis; 2) Methods: an analytic cross-sectional design collected retrospectively from medical record data from July 2023 to December 2024; 3) Results: A total of 30 neonates with probable sepsis met the inclusion criteria. Most cases were classified as early-onset sepsis (86.67%). Sepsis was more frequently observed in neonates with normal birth weight (53.3%), term gestational age, and those delivered by cesarean section (60.0%). No significant association was found between maternal age, gestational age, or method of delivery and sepsis classification. However, birth weight was significantly associated with sepsis classification (p < 0.05). The most commonly used empiric antibiotic regimen was ampicillin–sulbactam combined with gentamicin (60.6%). No significant association was found between empiric antibiotic use and clinical outcomes (p = 0.76; OR = 1.55; 95% CI: 0.09–27.36) or length of hospital stay (p = 0.71; OR = 1.43; 95% CI: 0.22–9.38) 4) Conclusions: Penicillin–aminoglycoside was the most commonly used empiric regimen and was generally appropriate based on the Gyssens criteria. However, no significant association was found between empiric antibiotic use and clinical outcomes.